Spotlighting a Silent Category of Young Females: The Life Experiences of ‘House Girls’ in Turkey - Çelik, K.; Lüküslü, D. (Sage Publications Inc, 2012)
This article examines the everyday life experiences of young women in Turkey known as ev ki{dotless}zi{dotless} or "house girls." The article explores how traditional gender roles and family structure in Turkish society limit their full participation in political, economic, and public life. The study is based on in-depth interviews conducted with a total of 30 young women who are house girls from a district in Istanbul and another district in Ankara. The women interviewed were between the ages of 18 and 24, single, living with their family, and not engaged in full-time education or employment. Historically contextualizing gender-related development in Turkey, the differences in access to full citizenship among two groups of women based on factors including levels of education, rural/urban divide, socialization, adherence to traditional family values of obedience, loyalty to parents, and the like and drawing on quotes from interviews, the article describes the ways that the experiences of house girls are constrained by traditional gendered expectations compared with other women in Turkey. Expectations of house girls includes fulfilling family obligations at home, conforming to specified codes of behavior, remaining virgin until marriage, and not participating in the formal educational system or the labor market. The authors argue that, compared with students or working women, house girls are restricted to the private sphere. This leads them to feel a sense of boredom, low self-worth, lack of economic empowerment, and inability to fully participate in the public sphere of contemporary Turkish society. The authors also underline the gap between youth studies and women's studies and argue that the study of house girls is well situated for addressing this gap. © 2012 SAGE Publications.
Keywords: Everyday Life Experiences; Exclusion; Young Women